Efeito de Diferentes Níveis de bicarbonato de sódio sobre a degradação in situ do bagaço de cana-de-açucar auto-hidrolisado - Bergamaschine, A. F.; de Andrade, P.; Valerio, W. V. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1997)
The objective of this work was to evaluate the buffering effects, using sodium bicarbonate (NaHCO3) at the levels: 0; 0.7; 1.4; and 2.1% of dry matter, on the in situ degradation of autohidrolised sugar-cane bagasse. A diet was used with 60% autohidrolised sugar bagasse (AHB) and 40% of concentrate, plus urea, minerals and limestone. The rations was calculated to allow 300g of daily gain. After 20 days adaptation to the treatment (level of NaHCO3), 5 g of AWE was incubated on rumen of four bovines for 3, 6, 12, 24 and 48 hours, using naylon bag measuring 7,5 x 17,5 cm with pores of 36 micras. It was used a randomized blocks design with four treatments (NaHCO3) and four replications(animals). For the calculations of the protein degradation, it was considered the soluble fraction in water plus the degraded fraction in the same proportion as for the neutral detergent fiber (NDF). It was observed that the buffer did not affect the degradability in situ of AHB, whose averages in 48 hours of incubation for dry matter, organic matter, crude protein and neutral detergente fiber (NDF) were 34.83; 36.90; 55.40; and 25.56%, respectively.
Effect of different levels of sodium bicarbonate on the degradability in situ of the autohydrolised sugar-cane bagasse
Keywords: autohydrolised sugar-cane bagasse; sodium bicarbonate; in situ degradability